Banquet Scenes of the Late Hittite Period - Coşkun, İsmail (Atlas Journal, 2024)
The Late Hittite period is marked by the emergence of independent city-states in southern and southeastern Anatolia following the collapse of the Hittite Empire. This cultural heritage not only preserved Hittite traditions but also incorporated artistic and ritualistic elements influenced by Assyrian and Aramean cultures, creating a richly diverse legacy. Banquet scenes from this era offer crucial insights into the social, religious, and ritualistic life of the time. These scenes are often depicted on stone reliefs, seals, and valuable objects. They commonly portray kings and queens seated at lavishly adorned tables, surrounded by attendants and accompanied by musicians. Significant examples of such depictions can be found in regions like Karatepe, Zincirli, and Karkamış. For instance, the reliefs from Zincirli depict a king seated on a throne, holding a goblet, with an array of sumptuous dishes displayed before him. Additionally, scenes from Tell Tayinat highlight sacrificial ceremonies and feasts dedicated to the gods. The artistic style of these works reveals a progression from traditional Hittite motifs to Assyrian influences. Early depictions feature cross-legged tables and characteristic Hittite styles, while later scenes display rectangular tables and motifs inspired by Assyrian art. These banquet scenes serve not only as artistic expressions but also as visual documentation of social hierarchy, religious beliefs, and cultural transformations. The banquet scenes of the Late Hittite period provide invaluable insights into the social structure, religious practices, and intercultural dynamics of the time, making them essential resources for archaeological and historical research.